2013
DOI: 10.1186/1471-2164-14-802
|View full text |Cite
|
Sign up to set email alerts
|

Identification of phenylpropanoid biosynthetic genes and phenylpropanoid accumulation by transcriptome analysis of Lycium chinense

Abstract: BackgroundLycium chinense is well known in traditional Chinese herbal medicine for its medicinal value and composition, which have been widely studied for decades. However, further research on Lycium chinense is limited due to the lack of transcriptome and genomic information.ResultsThe transcriptome of L. chinense was constructed by using an Illumina HiSeq 2000 sequencing platform. All 56,526 unigenes with an average length of 611 nt and an N50 equaling 848 nt were generated from 58,192,350 total raw reads af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…PAL catalyses the first step of the phenylpropanoid pathway, which is required for biosynthesis of many phenolic secondary metabolites (Fig. A: modified from Zhao et al ., ). To determine how virus infection alters the production of metabolites generated through the phenylpropanoid pathway, we conducted a metabolomic analysis of SCMV‐infected and mock‐inoculated maize leaves.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…PAL catalyses the first step of the phenylpropanoid pathway, which is required for biosynthesis of many phenolic secondary metabolites (Fig. A: modified from Zhao et al ., ). To determine how virus infection alters the production of metabolites generated through the phenylpropanoid pathway, we conducted a metabolomic analysis of SCMV‐infected and mock‐inoculated maize leaves.…”
Section: Resultsmentioning
confidence: 97%
“…SCMV infection triggered increased production of multiple phenylpropanoid pathway metabolites including 3,4‐dihydroxycinnamic acid, 4‐hydroxycinnamic acid, ferulic acid, caffeic acid, chlorogenic acid and naringenin. Significantly, ferulic acid, caffeic acid and chlorogenic acid are the intermediates of lignin biosynthesis (Barrière et al ., ; Shine et al ., ; Silverman et al ., ; Zhao et al ., ). Consistent with this, our results showed that SCMV‐infected maize plants accumulated more lignin but this occurred at a later stage of infection than peak accumulation of SA.…”
Section: Discussionmentioning
confidence: 97%
“…These are involved in various activities such as UV filtration, fixing atmospheric nitrogen, and protection of cell walls (Zhao et al, 2013). Analysis of soybean mutant defective in seed coat led to identification of differentially expressed proline-rich and other cell wall protein transcripts (Kour et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Zhao et al. () identified 11 genes associated with phenylpropanoid biosynthesis pathway using next‐generation sequencing in Lycium chinense . We screened all the genes involved in phenylpropanoid biosynthesis in jute and developed SSR markers for several key genes including PAL , CCoAOMT , C4H, CHI, FLS, F3H and LDOX covering almost all the steps of phenylpropanoid biosynthesis in jute.…”
Section: Discussionmentioning
confidence: 99%